Analysis of pregnancy outcomes in patients with recurrent implantation failure complicated with chronic endometritis - Li, Jie; Li, Xueyao; Ding, Jinli; Zhao, Jing; Chen, Jiao; Guan, Feng; Deng, Haiyu; Zhou, Mengqi; Han, Yiling; Xiao, Zhuoni; Yang, Jing (Frontiers in Cell and Developmental Biology, 2023)
Can antibiotic and PRP treatment improve pregnancy outcomes of freeze-thaw embryo transfer (FET) in patients with repeated implantation failure (RIF) complicated with chronic endometritis (CE)? 327 patients, who received assisted reproductive technology treatment at Reproductive Center of Wuhan University Renmin Hospital, Hubei, China, between January 2018 to January 2020, with RIF were recruited and their endometrium specimens in mid-luteal period were collected. Patients were divided into persistent weak positive CE (+) group, CE (-) group and non-CE group, according to the infiltration of Mum-1+/ CD138+ plasmacytes after antibiotic and PRP treatment. FET was performed and the basic characteristics and pregnancy outcomes of patients in 3 groups were compared.Among 327 RIF patients, 117 patients were complicated with CE, the prevalence was 35.78%. The prevalence of strong positive was 27.22% and that of weak positive was 8.56%. 70.94% patients with CE converted to negative after treatment. There was no significant difference in the basic characteristics, including age, BMI, AMH, AFC,infertility years, infertility types, number of previous transplant cycles, endometrial thickness on transplantation day and number of transplanted embryos (P > 0.05); The positive rate of hCG, clinical pregnancy rate and implantation rate in CE (-) group were significantly increased compared with the weak CE (+) group and non-CE group (P<0.01), and the live birth rate also improved (P<0.05). Whereas, the rate of early abortion in CE (-) group was 12.70%, which was higher than that in weak CE (+) group and non-CE group (P<0.05). It is recommended to perform CE-related examination for patients with RIF. Antibiotic and PRP treatment can significantly improve pregnancy outcomes of patients with CE negative conversion in FET cycle.